Efficacy of dendritic cell-based vaccine on acute myeloid leukaemia in a murine model - Ng, Wei Yi (2013)
Acute myeloid leukaemia (AML) has a high rate of relapse despite current chemotherapy and haematopoietic stem cell transplantation. This emphasizes the need of alternative therapeutic strategies in improving the long-term survival of AML patient. Dendritic cells (DCs) are professional antigen presenting cells that able to elicit specific T cell immunity. Their use in immunotherapy is to direct immune response against residual tumour cells and eventually lead to complete tumour eradication. This unique capability of DCs renders them as an attractive adjunct for the treatment of AML. Therapeutic efficacy of syngeneic DC-based vaccine alone or in combination with chemotherapy to eradicate AML was evaluated in vivo. DCbased vaccine were generated in vitro by culturing murine bone marrow cells in the presence of granulocytes-macrophages colony-stimulating factor (GM-CSF), interleukin-4 (IL-4) and tumour necrosis factor-α (TNF-α) and subsequently DC were pulsed with AML cell (C1498) lysate at a ratio of one DC to three AML cells.In vitro data showed that generated DC-based vaccine was functionally intact with the capability to induce T cell proliferation and elicit cytotoxicity effect against murine C1498 cell line. In vivo experiments carried out on groups of 6 mice showed that monotherapy with Ara C alone failed to control tumour growth. Although DCbased vaccine monotherapy was also able to control aggressive tumour development (P < 0.05; Man-Whitney Test), it provided only minimal survival benefits with median survival time (MST) of 12 days compared to 10 days with PBS treatment. In contrast, the antitumour effect was enhanced by combination therapy when Ara C treatment was given prior to DC-based vaccine treatment (AraC-DC) (P < 0.10; Man- Whitney Test) with MST greatly improved to 15 days. Strikingly, repeated combined therapy by intervening DC-based vaccine treatment preceding Ara C treatment and a repeat of DC-based vaccine (DC-AraC-DC) showed greater antitumour effect and dramatically improved long term survival (MST of 20 days) of AML mice than in response to either monotherapy alone (P < 0.05; Man-Whitney Test) or combined therapy (P < 0.05; Man-Whitney Test). These novel findings reveal the value of incorporating DC-based vaccine with cytosine arabinoside at different treatment schedule in treating AML patient clinically.